Management of Chronic Kidney Disease-Mineral and Bone Disorder (CKD-MBD) - Nugroho, Pringgodigdo (Jurnal Penyakit Dalam Indonesia, 2021)
Chronic kidney disease (CKD) is still a burden on worldwide health issues affecting about 11-13% of the general population. Chronic kidney disease-mineral and bone disorder (CKD-MBD) is a common complication in CKD, which occurs early in the disease, and progresses as kidney function deteriorates. With declining kidney function, mineral homeostasis becomes progressively dysregulated, including alterations in several parameters such as calcium, phosphate, intact parathyroid hormone (iPTH). Changes in these parameters are associated with bone disorders and vascular abnormalities, which are strongly correlated with increased cardiovascular (CV) morbidity and mortality, and overall mortality. Currently, CKD-MBD and its complication management have been focusing on correcting biochemical and hormonal abnormalities to limit their potential effects. All therapeutic decisions are based on circulating levels of calcium, phosphate and PTH considered together. CKD-MBD management should also be individualized since it might differentially benefit the patients.